The serotonin transporter linked polymorphic region and brain-derived neurotrophic factor valine to methionine at position 66 polymorphisms and maternal history of depression: Associations with cognitive vulnerability to depression in childhood. (August 2013) - Hayden, Elizabeth P.; Olino, Thomas M.; Bufferd, Sara J.; Miller, Anna; Dougherty, Lea R.; Sheikh, Haroon I.; Singh, Shiva M.; Klein, Daniel N.
Abstract: Preliminary work indicates that cognitive vulnerability to depression may be associated with variants of the serotonin transporter promoter polymorphism ( 5-HTTLPR ) and the valine to methionine at position 66 (val66met) polymorphism of the brain-derived neurotrophic factor ( BDNF ) gene; however, existing reports come from small samples. The present study sought to replicate and extend this research in a sample of 375 community-dwelling children and their parents. Following a negative mood induction, children completed a self-referent encoding task tapping memory for positive and negative self-descriptive traits. Consistent with previous work, we found that children with at least one short variant of the 5-HTTLPR had enhanced memory for negative self-descriptive traits. The BDNF val66met polymorphism had no main effect but was moderated by maternal depression, such that children with a BDNF methionine allele had a heightened memory for negative self-descriptive traits when mothers had experienced depression during children's lifetimes; in contrast, children with a methionine allele had low recall of negative traits when mothers had no depression history. The findings provide further support for the notion that the 5-HTTLPR is associated with cognitive markers of depression vulnerability and that the BDNF methionine allele moderates children's sensitivity to contextual factors.